2007
DOI: 10.1039/b705227h
|View full text |Cite
|
Sign up to set email alerts
|

Designing Zn(ii) and Cu(ii) derivatives as probes for in vitro fluorescence imaging

Abstract: New M(II) bis(thiosemicarbazonato) complexes (M = Ni(II), Cu(II) and Zn(II)) featuring allyl groups at the exocyclic nitrogens have been synthesised. The complexes were characterised in solution by spectroscopic methods and their solid state structures determined by single crystal X-ray diffraction using synchrotron radiation. The Zn(II) complex was found to be intrinsically fluorescent and soluble in biocompatible media. The uptake of this Zn(II) complex in HeLa, MCF-7 and IGROV cancer cells was monitored by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
73
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 29 publications
0
73
0
Order By: Relevance
“…Two control groups were used consisting of 100 μL solvent/ well, i.e 1%: 99% EMEM, as well as 100% EMEM. FEK-4 and MCF-7 cell lines (cultured using standard procedures [106] ) were incubated at 37 °C with the samples prepared as above for 1 h, 3 h, 6 h and 24 h. After incubation, wells were aspirated and solvents replaced by 100 μL of 0.5 mg/mL MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) in EMEM:PBS 9:1, followed by a further incubation (at 37 °C) for 2 h. [107,108] The MTT solution was then aspirated and 100 μL of DMSO was added. Absorbance of resulting samples (directly proportional to cell viability) was measured at 570 nm using a plate reader.…”
Section: Cell Viability Tests In Fek-4 and Mcf-7 Cell Lines By Mtt Asmentioning
confidence: 99%
“…Two control groups were used consisting of 100 μL solvent/ well, i.e 1%: 99% EMEM, as well as 100% EMEM. FEK-4 and MCF-7 cell lines (cultured using standard procedures [106] ) were incubated at 37 °C with the samples prepared as above for 1 h, 3 h, 6 h and 24 h. After incubation, wells were aspirated and solvents replaced by 100 μL of 0.5 mg/mL MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) in EMEM:PBS 9:1, followed by a further incubation (at 37 °C) for 2 h. [107,108] The MTT solution was then aspirated and 100 μL of DMSO was added. Absorbance of resulting samples (directly proportional to cell viability) was measured at 570 nm using a plate reader.…”
Section: Cell Viability Tests In Fek-4 and Mcf-7 Cell Lines By Mtt Asmentioning
confidence: 99%
“…It was not until 2007 that Pascu et al [68] reported the first metal complexes of Zn(II) and Cu(II) based on acenaphthenequinone bis(thiosemicarbazone) ligands. The intrinsic fluorescence of the acenaphthene group in the backbone of the metal complex allowed the in vitro study of the uptake in different cancer cells.…”
Section: Multimodal Imagingmentioning
confidence: 99%
“…The generation process of 68 Ga is more straightforward and affordable for clinical applications, due to the use of a 68 Ge/ 68 Ga generator, which gives a readily available dose in a shorter time and which can be done in a clinical facility. Furthermore, 68 Ga t 1/2 is 68 minutes, which is in the desired range for an imaging experiment. The chemical process where the hot derivative is involved has to be rapid enough, but timing is not as crucial an issue as with 18 F, which has a t 1/2 of 109.7 min, and significantly more challenging multistep radiochemistry, in our experience.…”
Section: Multimodal Imagingmentioning
confidence: 99%
See 2 more Smart Citations